2019
DOI: 10.1242/jeb.212274
|View full text |Cite
|
Sign up to set email alerts
|

Differential construction response to humidity by related species of mound-building termites

Abstract: Macrotermes michaelseni and M. natalensis are two morphologically similar termite species occupying the same habitat across southern Africa. Both build large mounds and tend mutualistic fungal symbionts for nutrients, but despite these behavioural and physiological similarities, the mound superstructures they create differ markedly. The behavioural differences behind this discrepancy remain elusive, and are the subject of ongoing investigations. Here, we show that the two species demonstrate distinctive buildi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…We observed large colony-level variability in the measured mass (electronic supplementary material, figure S1), but a linear mixed model comparison testing colony as a random effect (table 2) still showed a significant difference in the mass displacement between the two treatments ( p < 0.01) [28]. The area of the plate covered by soil and the volumetric envelope (reconstructed using the 3D point cloud from the active depth sensor [24]) were also significantly different between treatments ( p < 0.01, figure 4e), though these are correlated with mass and may not represent qualitative differences in structure.…”
Section: (C) Shielded and Unshielded Build Sitesmentioning
confidence: 92%
See 1 more Smart Citation
“…We observed large colony-level variability in the measured mass (electronic supplementary material, figure S1), but a linear mixed model comparison testing colony as a random effect (table 2) still showed a significant difference in the mass displacement between the two treatments ( p < 0.01) [28]. The area of the plate covered by soil and the volumetric envelope (reconstructed using the 3D point cloud from the active depth sensor [24]) were also significantly different between treatments ( p < 0.01, figure 4e), though these are correlated with mass and may not represent qualitative differences in structure.…”
Section: (C) Shielded and Unshielded Build Sitesmentioning
confidence: 92%
“…Many termite species are vulnerable to desiccation, and forage below ground or construct soil envelopes around their food sources to shelter from environmental conditions [21]. Termites have been shown to sense humidity with their antennae [22] and cluster at zones of high humidity [23,24], suggesting that they may be able to sense a difference between the high humidity within their mounds and the lower humidity of the environment outside of them.…”
Section: Introductionmentioning
confidence: 99%
“… [59] , [74] ), the appearance of the mounds of Macrotermes bellicosus differ from forests, where mounds have a smooth and thick outer wall, to those in the open savannah, where mounds have rough ridges and thin outer walls. Differences appear to be driven by humidity, shown experimentally by Carey et al [75] . The porosity of the outer shell facilitates diffuse gas transport along concentration gradients while the small pore size makes the mound very resistant to pressure-driven bulk flow across its thickness with the mound surface acting like a breathable windbreaker [33] .…”
Section: Classification Of Termite Mounds and Morphologymentioning
confidence: 80%
“…7C and 8D), which may inhibit the feeding activities of C. formosanus. Likewise, Carey et al (2019) reported that the mound-building termites, Macrotermes michaelseni (Sjöstedt), performed different clay-relocation behaviors depending on the humidity levels, as they transport less soil and creates structures with smaller volumetric envelopes in the laboratory with low ambient humidity compared with high-humidity conditions.…”
Section: Discussionmentioning
confidence: 99%